2019
DOI: 10.1002/jsfa.9685
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of ultraviolet radiation and high hydrostatic pressure on texture, color, and oxidative stability of refrigerated tilapia fillets

Abstract: BACKGROUND: The isolated application of high hydrostatic pressure (HHP) and ultraviolet-C (UV-C) radiation may induce physicochemical changes, thus jeopardizing fish quality attributes during refrigerated storage, which could be minimized by the use of synergistic treatments. Therefore, this study investigated the combined effect of UV-C at 0.103 ± 0.002 J cm −2 and HHP at 220 MPa for 10 min on quality parameters of tilapia fillets stored at 4 ∘ C for 15 days. RESULTS: HHP and UV-C+HHP showed higher myoglobin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 56 publications
4
22
0
1
Order By: Relevance
“…In agreement with our results, previous studies reported a decrease in a* values during refrigerated storage of rainbow trout fillets [30] and pirarucu fillets [39], and also an increase of b* values in pirarucu fillets [39] and tilapia fillets [8,9] under refrigerated storage. Also, similar to our results, Pedrós-Garrido et al [42] and Lee et al [43] observed that UV-C radiation at 0.19-0.38 J/cm 2 and 4.8 J/cm 2 enhanced meat discoloration by the decrease in a* values and increase in b* values in salmon fillets and semi-dried Pacific herring, respectively.…”
Section: Instrumental Color Parameterssupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with our results, previous studies reported a decrease in a* values during refrigerated storage of rainbow trout fillets [30] and pirarucu fillets [39], and also an increase of b* values in pirarucu fillets [39] and tilapia fillets [8,9] under refrigerated storage. Also, similar to our results, Pedrós-Garrido et al [42] and Lee et al [43] observed that UV-C radiation at 0.19-0.38 J/cm 2 and 4.8 J/cm 2 enhanced meat discoloration by the decrease in a* values and increase in b* values in salmon fillets and semi-dried Pacific herring, respectively.…”
Section: Instrumental Color Parameterssupporting
confidence: 93%
“…The increase of L* values as the increase of storage period was found in other refrigerated freshwater fish species [9,13,39], including rainbow trout [30]. Likewise, similar UV-C doses (0.10 and 0.30 J/cm 2 ) and O 2 scavenger, alone or in combination, did not affect L* values of tilapia fillets stored under refrigeration [8,9,13], corroborating with our results. Table 3.…”
Section: Instrumental Color Parameterssupporting
confidence: 90%
See 3 more Smart Citations